European eel (Anguilla anguilla) time series - Gavioli, Anna; Aschonitis, Vassilis; Lanzoni, Mattia; Castaldelli, Giuseppe (Zenodo, 2024)
This dataset was managed for the aims of the project ECOSISTER (Ecosystem for Sustainable Transition in Emilia-Romagna), WP3 of Spoke 5 and provides the long-term records (from 1781 to 2013) of European eel (Anguilla anguilla L.) production in the Comacchio Lagoon (Italy). he European eel spends most of its life as a yellow eel in freshwater, brackish, and coastal environments. Upon reaching sexual maturity, it undergoes metamorphosis into a silver eel and migrates back to the Sargasso Sea to spawn and die. The silver eels of Comacchio Lagoon were always caught in the lavorieri with approximately 100% efficiency and official estimates of the total biomass were being made every year for more than 200 years. The Regional Park of the Po Delta and the Management Agency for the Parks and Biodiversity of Delta del Po were founded in 1988 and took over the infrastructures, official documents and records of the previous company managing the fishery. These fishery historical records were organized and combined with new data to provide 1) Annual records of total weight of silver eels captured and 2) Annual records that present the variation of fishing area coverage, from 1781 to 2013. The dataset is provided in two formats: - Microsoft Excel XLSX file, including 3 sheets (Dataset, Fields and units, Taxonomy) - CSV files (UTF-8), 3 files corresponding to the 3 sheets of the Excel file The dataset includes 233 records with total weight of silver eels captured in the Comacchio lagoon, their annual density, and the fishing area coverage. The fields are described in Table 1. All the dataset fields are described in the Excel sheet/CSV file “Fields and units”, while the taxonomic related information for Anguilla anguilla is provided in the Excel sheet/CSV file “Taxonomy”. Information extracted from the World Register of Marine Species (WoRMS; https://marinespecies.org/ ) is provided here (see details in Table 2). Table 1. Fields in the dataset (NA=not available). Field Darwin Core term Unit Precision Note decimalLatitude ...